Quantification of eccentric hamstrings strength in elite academy footballers: Considerations for assessment - Rhodes, D.; Greig, M.; Jeffrey, J.; Alexander, J. (Central European Journal of Sport Sciences and Medicine, 2023)
Quantification of eccentric hamstring strength within elite youth sporting populations is a contemporary issue within practice. The aim of the study was to identify the reliability of eccentric strength metrics obtained via isokinetic dynamometry (IKD) and the NordBord in an elite youth football population. Furthermore, relationships between the strength metrics exhibited by the two devices were observed, to ascertain whether level of performance on one device can indicate how athletes will perform on the other. Twenty-one elite academy footballers completed two measures of eccentric hamstring strength on each device (60°·s-1 and 180°·s-1). Test-retest reliability was determined through Pearson correlation analysis. Relationships between strength metrics (IKD: PT, AvT and oPT at 60°·s-1 and 180°·s-1; NordBord: PF, AvF, PT, AvT, O) obtained on both devices were identified for analysis. Test-retest of both devices identified significant correlations for all eccentric strength metrics (P==0.05). Significant unilateral (L) relationships between PT, AvT (IKD 60°·s-1; 180°·s-1), break angle (O) (NordBord) angle peak torque (oPT) at 60°·s-1 and O were identified (P==0.05). Eccentric hamstring strength analysis on both the IKD and NordBord provide reliable information for practitioners, justifying their inclusion as one factor that may inform readiness to train and injury risk, within elite youth footballers. Although, careful consideration in relation to individual metrics must be given when informing decision making processes. Practitioners require clarity on the objectives of the assessment, what the strength metrics represent and how they provide insight into performance and injury risk.